Cytosine methylation of sperm DNA in horse semen after cryopreservation - Aurich, Christine; Schreiner, Bettina; Ille, Natascha; Alvarenga, Marco [UNESP]; Scarlet, Dragos (Elsevier, 2016)
Semen processing may contribute to epigenetic changes in spermatozoa. We have therefore addressed changes in sperm DNA cytosine methylation induced by cryopreservation of stallion semen. The relative amount of 5-methylcytosine relative to the genomic cytosine content of sperm DNA was analyzed by ELISA. In experiment 1, raw semen (n = 6 stallions, one ejaculate each) was shock-frozen. Postthaw semen motility and membrane integrity were completely absent, whereas DNA methylation was similar in raw (0.4 ± 0.2%) and shock-frozen (0.3 ± 0.1%) semen (not significant). In experiment 2, three ejaculates per stallion (n = 6) were included. Semen quality and DNA methylation was assessed before addition of the freezing extender and after freezing-thawing with either Ghent (G) or BotuCrio (BC) extender. Semen motility, morphology, and membrane integrity were significantly reduced by cryopreservation but not influenced by the extender (e.g., total motility: G 69.5 ± 2.0, BC 68.4 ± 2.2%; P < 0.001 vs. centrifugation). Cryopreservation significantly (P < 0.01) increased the level of DNA methylation (before freezing 0.6 ± 0.1%, postthaw G 6.4 ± 3.7, BC 4.4 ± 1.5%; P < 0.01), but no differences between the freezing extenders were seen. The level of DNA methylation was not correlated to semen motility, morphology, or membrane integrity. The results demonstrate that semen processing for cryopreservation increases the DNA methylation level in stallion semen. We conclude that assessment of sperm DNA methylation allows for evaluation of an additional parameter characterizing semen quality. The lower fertility rates of mares after insemination with frozen-thawed semen may at least in part be explained by cytosine methylation of sperm-DNA induced by the cryopreservation procedure.
Keywords: Cryopreservation; DNA methylation; Horse; Semen